Knowledge, attitude and practice of antenatal care among pregnant women attending antenatal clinic in a tertiary care hospital of Mathura, Uttar Pradesh, India - Garg, Parul; ., Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to assess the knowledge, attitude and practice of antenatal care among pregnant women attending antenatal clinic in a tertiary care hospital and also to identify factors that are associated with non-usage of antenatal care. Methods: The study was conducted on 150 pregnant women attending antenatal clinic in department of obstetrics and gynecology of K. D. Medical College and associated hospital of Mathura from September 2019 to December 2019. After obtaining consent, randomly selected pregnant women were given a pre-designed, structured questionnaire on socio-demographic variables, knowledge, attitude and practice towards antenatal care. Results: In the present study, out of 150 respondents, 62.7% had knowledge and awareness regarding antenatal care. There was inadequate knowledge about frequency of antenatal visits with 59.3% subjects wanting to deliver in the hospital. Conclusions: To improve effective utilization of ANC services, we need to bring behaviour changes, improve communication and quality of service delivery, along with effective monitoring and evaluation. Awareness should be developed in the community about the importance of registration for ANC, educating women about the detection of complications during pregnancy, importance of TT injection, IFA tablets and extra nutrition.